Dual series method for solving Helmholtz equation with mixed boundary conditions of the third kind - Hoshan, Naser (International Journal of Applied Mathematical Research, 2014)
The paper involves with the application of the dual series equation to the problem of Helmholtz equation of cylindrical coordinates subject to inhomogeneous mixed boundary conditions of the third kind located on the surface of the cylinder of bounded radius and infinite high. By choosing the Hankel integral transform, the dual series equations were reduced to a Fredholm integral equation of the second kind which is solved conveniently by using numerical techniques. Keywords: Helmholtz Equation, Dual Series Equations, Mixed Boundary Conditions.